Linux pocket guide - Barrett, Daniel J. (O'Reilly Media, 2012)
If you use Linux in your day-to-day work, this popular pocket guide is the perfect on-the-job reference. The second edition has expanded from Fedora-only coverage to distro-neutral, with practical information on a wider range of commands requested by readers. For novices who need to get up to speed on Linux use, and experienced users who want a concise and functional reference, this guide provides quick answers.